Representation in Kenya, Its Diaspora, and Academia: Colonial Legacies in Constructions of Knowledge About Kenya's Coast - Jesse Benjamin (Journal of Global Initiatives, 2010)
This paper explores the construction of knowledge in Kenya in the context and aftermath of colonialism and underdevelopment. Those communities that were politically and economically marginalized in Coast Province over the past century were also displaced in terms of academic opportunities, resulting in fewer social science scholars from Mijikenda and other non-Swahili communities in both Kenyan and diaspora universities. Underdevelopment studies in Africa and Kenya are briefly reviewed, and the colonial history of asymmetric social relations at coastal Kenya is traced. Finally, key debates over identity and history are examined within this context and shown to be exacerbated by diasporic Kenyan scholars, further reinforcing trajectories of unequal social relations in Kenya.